2010
DOI: 10.1523/jneurosci.4893-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Pentraxins Mediate Silent Synapse Conversion in the Developing Visual System

Abstract: Neuronal pentraxins (NPs) are hypothesized to play important roles in the recruitment of AMPA receptors (AMPARs) to immature synapses, yet a physiological role for NPs at nascent synapses in vivo has remained elusive. Here we report that the loss of NP1 and NP2 (NP1/2) leads to a dramatic and specific reduction in AMPAR-mediated transmission at developing visual system synapses. In thalamic slices taken from early postnatal mice (ϽP10) NP1/2 knock-out (KO) neurons displayed severely reduced AMPAR-mediated reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 51 publications
2
45
0
Order By: Relevance
“…2F and G). The first of these, Gm21781, is upstream of a gene that encodes a DNA binding protein known as zinc finger and BTB domain containing 2 ( Zbtb2 ), which has been shown to be a potent epigenetic regulator (55), and the second, Gm11762, is antisense to neuronal pentraxin 1 ( Nptx1 ), which has been reported to enhance synaptogenesis and glutamate signalling through clustering of AMPA receptors (56). Finally, we observed a significant down-regulation of the neuropsychiatric disease-related lncRNA Gomafu in the mPFC, which occurred following fear conditioning but not after context exposure (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2F and G). The first of these, Gm21781, is upstream of a gene that encodes a DNA binding protein known as zinc finger and BTB domain containing 2 ( Zbtb2 ), which has been shown to be a potent epigenetic regulator (55), and the second, Gm11762, is antisense to neuronal pentraxin 1 ( Nptx1 ), which has been reported to enhance synaptogenesis and glutamate signalling through clustering of AMPA receptors (56). Finally, we observed a significant down-regulation of the neuropsychiatric disease-related lncRNA Gomafu in the mPFC, which occurred following fear conditioning but not after context exposure (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The use of ligand-activated Cre allowed us to control the number of cells labeled in the retina by titrating the dose of tamoxifen administered, and thus visualize single-cell morphology (Figure 1B-E). BD-RGC axon arbors target the area where we and others have previously characterized retinogeniculate synaptic refinement by slice electrophysiology (Chen and Regehr, 2000; Jaubert-Miazza et al, 2005; Koch and Ullian, 2010; Stevens et al, 2007). By focusing on one RGC subtype, structural heterogeneity arising from the existence of multiple RGC subtypes can be minimized.…”
Section: Resultsmentioning
confidence: 99%
“…Mutants of the immune system molecules, H2Db, have impaired LTD after patterned stimulation mimicking endogenous retinal waves [114]. Along similar lines, it was shown that neuronal pentraxins 1 and 2 (NP1/2) are required for the normal development of AMPAR-mediated transmission and could convert silent synapses during eye-specific refinement [115]. The discovery of all these immune system molecules that are regulated by activity has gained more weight and has also implied new players such as microglia and astrocytes in synaptic refinement.…”
Section: Immune System Molecules Glia and Microgliamentioning
confidence: 88%